Stable isotopes of 18O and D in key components of water flows and the permafrost zone of Central Yakutia (Eastern Siberia) - A. A. Galanin; M. R. Pavlova; T. S. Papina; A. N. Eyrikh; N. A. Pavlova (Лëд и снег, 2019)
On the basis of about 430 analyses, the 18O and D compositions (%o) of atmospheric precipitation, ground ice, surface and inter-permafrost underground waters of cryogenic-aeolian landscapes of Central Yakutia (Eastern Siberia) are discussed. Precipitation compositions here demonstrate a large annual variation (from -6.12 to -45.0 % for δ18O, and from -72.1 to -350.1 % for δD), and they are described by the Local Meteoric Water Line according to the equation δD = 7.81518O - 1.57). In winter and in the process of spring melting, the snow storage is subjected to a significant evaporative fractionation, that is expressed by the equation δD = 6.85518O - 31.9. The heaviest and deuterium-depleted compositions (δ18O = -19.3 %, δD = -160.9, dexc = -6.7 %) are found in the last snow patches in early June. The lightest compositions similar to the present-day winter precipitation (snow) are characteristic of the polygonal wedge ices (PWI) of the Central Yakutia. The most lightweight (from -30 to -34 % for δ18O, and from 240 to 275% for δ D) were established to be typical for the ancient PWI, dated by the first half of the Late Pleistocene (MIS 3-4). Heavier compositions (δ18O = -27.2±1.4, δD = -215.8±8.5, dexc = 1.7±3.1 %) with obvious features of evaporative fractionation correspond to younger PWI (MIS 2-1). The heaviest compositions (δ18O = -12.2±0.7, δD = -99.2±4.7, dexc = -2.0±0.8 %) and high angular coefficients of approximating equations were determined in the investigated cave ices of sublimation origin, that implies the atmospheric origin of them. The current processes of evaporative fractionation are the most intensively reflected in the waters of aeolian lakes (δ18O = -11.8±3.5, δD = -120.2±18.4, dexc = -25.8±10.5 %), and the compositions are described by the regression equation 5D = 5.52 δ18O - 54.12 (R2 = 0.97). The phenomenal objects of the cryogenic-eolian landscapes of the Central Yakutia are high-debit underground sources. Among all other components of the water flows, composition of these sources is the most stable (δ18O = -21.6±0.8, δD = -172.6±5.1, dexc = 0.23±3.0 %). The regression of compositions of the largest underground source Bulus is approximated by the equation 5D = 6.31 δ18O - 36.7 (R2 = 0.78), that is indicative to significant evaporative fractionation and close relation with the aeolian lakes in the alimentation area.